Cultural Planning and Community Sustainability: The Case of the Cultural Facilities Plan of Catalonia (PECCAT 2010-20) - Martínez i Illa, Santi; Rius i Ulldemolins, Joaquim (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2011)
The government of Catalonia has developed a planning framework that seeks to establish the provision of cultural facilities throughout the country. The Cultural Facilities Plan of Catalonia (PECCAT) is based on an analysis of historical gaps and establishes a minimum spatial scheme. The plan responds to problems associated with the absence of a former similar instrument, which has led to an inconsistent and inappropriate cultural infrastructure that fails to fulfill its fundamental mission of securing the cultural rights of the population.The paper sets forth the aims of this policy and describes the objectives and basic characteristics of the plan and the expected outcomes. With the plan, the government of Catalonia seeks to rebalance the infrastructure within the territory and to ensure universal access to basic cultural services, while avoiding a logic of standardization and taking local communities into account. With the development of local plans in the municipalities, local governments encourage community participation processes to adapt and decide on priorities for action based on needs assessments and cultural opportunities for local sustainable development. The local plans focus on local cultural strengths, take advantage of opportunities, and aim to realize the cultural dynamics of a place through establishing an infrastructure that can best respond to the needs and cultural demands of the local communities, taking into account economic, social, and environmental sustainability.